The painter who changed her brain at the flick of a switch. Issue 4 (4th July 2021) - Fornazzari, Luis; Tan, Yu Bin; Haladyn, Julian; Bharatha, Aditya; Barfett, Joseph; Wilson-Sanchez, Maya; Afroz, Nausheen; Fischer, Corinne E.
ABSTRACT: The study of artists with acquired brain damage is an empirical way to investigate the multiplicity of cerebral changes that occur with artistic training. We describe a talented painter with a left progressive cerebral lesion. In spite of losing function of her right hand, she regained dexterity of the left one in ten days for painting and drawing but not for writing. We discuss two potential explanations for her rapid recovery: (a) her extensive artistic training and/or (b) the slow-growing nature of her cerebral lesion.